2017
DOI: 10.1007/s00330-017-5031-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimising preoperative risk stratification tools for prostate cancer using mpMRI

Abstract: PurposeTo improve preoperative risk stratification for prostate cancer (PCa) by incorporating multiparametric MRI (mpMRI) features into risk stratification tools for PCa, CAPRA and D’Amico.Methods807 consecutive patients operated on by robot-assisted radical prostatectomy at our institution during the period 2010–2015 were followed to identify biochemical recurrence (BCR). 591 patients were eligible for final analysis. We employed stepwise backward likelihood methodology and penalised Cox cross-validation to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Nomogram of the models was also established to evaluate their prognosis performance [ 30 ]. Decision curve analysis was performed for comparing the net benefits at different threshold probabilities given by the models [ 31 ]. The net reclassification improvement (NRI) and the integrated discrimination improvement (IDI) were also quantified for evaluating the prognostic benefit improvement of the PIM.…”
Section: Methodsmentioning
confidence: 99%
“…Nomogram of the models was also established to evaluate their prognosis performance [ 30 ]. Decision curve analysis was performed for comparing the net benefits at different threshold probabilities given by the models [ 31 ]. The net reclassification improvement (NRI) and the integrated discrimination improvement (IDI) were also quantified for evaluating the prognostic benefit improvement of the PIM.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some features of MRI, such as suspicious ECE, SVI, and regional lymph node metastasis, provide an important preoperative reference for RP surgery and lymph node dissection 21 . Some MRI indicators have been confirmed to be related to BCR after RP, such as the Likert score 22 and ADC value 23 . And some studies have also added clinical data to predict the risk of BCR after RP, 24 but few studies have applied mpMRI features combined with pathological data of fusion biopsy to the forecast of BCR and prognosis after RP.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that mpMRI can significantly reduce the number of unnecessary repeat prostate biopsies (45). Some researchers have tried to use mpMRI to determine risk stratification for PCa patients (46). The results showed that the fusion of mpMRI data and clinicopathological data can significantly improve the predictive model's ability to predict the recurrence of PCa disease, compared to traditional predictive models that only have clinical data.…”
Section: Discussionmentioning
confidence: 99%